Effects of diet on blood rheological indices, cytokine concentrations, and emergence of metabolic disorders in the persons with increased body mass index - P. S. Novikov; N. A. Cherevko; V. V. Klimov; S. E. Kondakov; M. Yu. Rozenshteyn; A. Z. Rozenshteyn; E. A. Motlokhova; D. S. Zagreshenko (Медицинская иммунология, 2022)
Metabolic syndrome (MS) is a serious medical and social problem due to its high prevalence, lack of common approaches to diagnosis and treatment. Prevention of food dysadaptation reactions and the studies of control mechanisms of immune tolerance to food antigens is of special scientific interest, thus providing available anti-inflammatory tools for correcting increased permeability of the intestinal epithelium and vascular endothelium associated with development of MS. Nutritional dysadaptation occurs due to inappropriate diet being mediated by the geno-phenotypic characteristics of digestive enzymes and immune system which control the efficiency of food digestion.Immunological control of digestion, including dynamic maintenance of tolerance to food antigens, is carried out at two levels of immune system: innate response with functional involvement of microbiota, and adaptive response, represented by cellular and humoral mechanisms associated with molecular epitopes and critical mass of persistent food antigens which are present in immunologically competent areas of small intestine, due to changing permeability of intestinal barrier and transcytosis processes. Patients and methods: aiming for assessment of the diet contribution to the immuno-biochemical and rheological imbalance in people with increased body weight, 170 volunteers of both sexes aged 20-55 years were examined, depending on the body mass index: > 27.0 kg/m2 (clinical group, n = 120), and those with BMI of < 25.0 kg/m2 (control group, n = 50). We have revealed statistically significant increase of multiple parameters in the clinical group, i.e., concentration of IL-6, IL-17, cholesterol, glucose, glycosylated hemoglobin, insulin, indices of insulin resistance and atherogenicity. Increased levels of specific IgG antibodies to a number of food antigens were found in the subjects in the clinical group. In the course of our study, a statistically significant relationships was found between total numbers of platelets (p < 0.05; r = 0.213), erythrocytes (p < 0.05; r = -0.211), mean erythrocyte volume (MCV) (p < 0, 05; r = 0.339), and the concentration of IgG to casein in the blood, as well as a correlation between the levels of sIgG to soybeans and the number of platelets (p < 0.05; r = 0.231). At the same time, some associations were found between the established values of IgG to casein pAG, and the risk of developing atherogenic changes (atherogenicity index > 3) being significant at OR = 2.68 (1.33-5.42), as well as between IgG values to casein pAG (OR = 8.9 (2.6-30.5)), to soybean pAG (OR = 5.6 (1.8-16.7)), to gluten pAG ((F = 0.00359. p < 0.05), and increased body mass index.The results obtained were interpreted as a possible impairment of food tolerance for a number of food antigens in individuals with high body mass index, due to the revealed correlations between concentrations of IgG to food antigens, imbalance of pro-inflammatory cytokines, rheological and metabolic parameters. These data may be used as biomarkers suggesting higher risk of evolving metabolic syndrome.